Pengaruh Pendidikan, Gender, dan Pengangguran terhadap Indeks Pembangunan Manusia di Kalimantan Tengah - Haga, Ronni; Rian Sidiq Prakoso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study analyzes the effect of the Gender Empowerment Index and the Open Unemployment Rate on the Human Development Index in Central Kalimantan, with the Realization of years of schooling as a mediating variable. The analysis method used is WarpPLS 7.0 to test the relationship between variables. The results of the study indicate that the Gender Empowerment Index and the Open Unemployment Rate have a significant effect on the Realization of years of schooling, which ultimately affects the Human Development Index. Although the direct effect of the Gender Empowerment Index and the Open Unemployment Rate on the Human Development Index is not significant, the indirect effect through the Realization of years of schooling shows a strong and significant relationship. These findings emphasize the importance of education as a key factor in improving the quality of life of the community, which is reflected in the Human Development Index. This study also reveals that policies that support gender empowerment and reduce unemployment can contribute to improved education and better human development, in line with sustainable development goals.